Magazine advertisement : to what extent does it influence purchasing decision in regards to fashion among the career women in Kota Kinabalu / Wahidah Magbool Rehmoon - Magbool Rehmoon, Wahidah (2007)
The purpose of this research is to know "Magazine advertisement: To what extent does it influence purchasing decision in regards to fashion among career women in Kota Kinabaiu". The total respondents taken in this survey are 150 and are selected among the working women ranging in various industries: private and government sector. Why women? Women are "born to shop" and their awareness of fashion is actually a responsibility to them to make them feel confident. Fashion for women are more interesting and complicated than men and as evidence there are few magazines for men and dozens for women.